Analisis Yuridis Tindak Pidana Pemerasan oleh Bendesa Adat Terhadap Investor di Bali - Anak Agung Sagung Laksmi Dewi; I Gusti Agung Ayu Gita Pritayanti Dinar; Ni Putu Ayu Mandalay Shasa Alba Chiara; Anak Agung Ngurah Adhi Wibisana (Fakultas Hukum, Universitas Warmadewa, 2025)
Customary village leaders, as organizers of government affairs at the village level, have the authority to complete administrative documents needed by the community within the government system of the rule of law. Occasionally, there are several obstacles in the completion of these administrative tasks that can be resolved quickly to facilitate administrative activities; however, certain administrative issues remain unsolvable by local administrators. The problem formulated in this study includes: (i) how are criminal sanctions defined for the crime of extortion corruption committed by Bendesa Adat who abuse their power in Bali? (ii) What sanctions are imposed on Bendesa Adat by customary villages when they exploit their power through extortion against investors? This study employs normative legal research methods, utilizing a legislative approach and legal concept analysis. The relevant data collection techniques utilized in this study consist of: (i) literature review and (ii) data analysis and evaluation. The theories applied in examining the issues within this study are the theory of state sovereignty and the conception of law as a policy process. This study aims to establish that criminal sanctions for extortion crimes by Bendesa Adat in Bali can indeed be determined. It is vital to implement a consistent and professional approach based on justice, certainty, and legal benefits by the government to foster ideal investment growth in Bali. The output target is to publish findings in the Sinta 4 accredited national journal, Journal of Legal Preferences. Additional outputs will include study materials (book chapters) related to criminal law topic.